Status and influencing factors of e-Health literacy among middle-aged and elderly people in rural areas of Suizhou City, Hubei Province, China (农村地区中老年人电子健康素养现状及影响因素研究) - LIU Qingyuan (刘情缘); DU Heng (杜恒); Hu Longyou (胡龙友); Quan Wenjing (全文静); Gao Jin (高进); XU Jianghua (徐江华) (Journal of International Translational Medicine Limited, 2024)
Objective To investigate the status of e-Health literacy among middle-aged and elderly people in rural areas, and to analyze its influencing factors, so as to provide a theoretical basis for improving the e-Health literacy among middle-aged and elderly people. Methods From July to August 2022, a questionnaire survey was conducted on 355 middle-aged and elderly people in rural areas of Suizhou City, Hubei Province, using a general information questionnaire and an e-Health literacy scale. Results The total e-Health literacy score of middle-aged and elderly people was (25. 94±6. 01). The results of multiple linear regression analysis showed that trust in online health information (β=0. 294), whether to actively obtain health information through the Internet (β=0. 186), gender (β=-0. 140), education level (β=0. 135), marital status (β=0. 114) were the main factors influencing e-Health literacy among rural middle-aged and older adults. Conclusion The e-Health literacy level of middle-aged and elderly people in rural areas of Suizhou City, Hubei Province was low. Under the situation of rapid development of ageing and health information technology, basic health services need to pay more attention to the e-Health literacy of rural middle-aged and elderly people and to seek a health service model for rural middle-aged and elderly people that is compatible with the development of the digital age. (目的 了解农村地区中老年人电子健康素养现状, 分析其影响因素, 为提高农村地区中老年人电子健康素养提供依据。方法 2022年7月-8月, 采用一般资料问卷、电子健康素养量表对湖北省随州市355名农村中老年人进行问卷调查。结果 湖北省随州市农村地区中老年人电子健康素养总分为(25. 94±6. 01)分。多重线性回归分析结果显示: 对网络健康信息的信任程度(β=0. 294)、是否主动通过网络获取健康信息(β=0. 186)、性别(β=-0. 140)、文化程度(β=0. 135)、婚姻状况(β=0. 114)是影响农村中老年人电子健康素养的主要因素。结论 湖北省随州市农村地区中老年人电子健康素养水平较低, 在人口老龄化与健康信息化快速发展的形势下, 基层卫生服务机构应重视农村中老年人电子健康素养, 积极寻求与数字时代发展相适应的农村中老年人健康服务模式。)